The Prospects of Sentencing Artificial Intelligence Based Autonomous Agents - Faizin Sulistio; Haru Permadi; Achmad Aldy Hifdillah; Oppy Pramudya Wisnu Wardhana (JURNAL AKTA, 2026)
This research examines the prospect of criminalizing autonomous agents based on Artificial Intelligence (AI) from the perspective of Indonesian criminal law. The object of research focuses on autonomous AI agents that are capable of operating and making decisions independently. The research objective is to analyze the legal challenges arising from AI's ability to perform potentially unlawful acts, as well as explore potential approaches in formulating an appropriate legal framework. The method used was doctrinal and comparative analysis, reviewing legal literature, policies, and global best practices related to AI regulation. The results show that Indonesia's current criminal law system is inadequate to accommodate the complexities of autonomous AI agents. Key challenges include the concept of mens rea, appropriate forms of sanctions, and determining the subject of liability. This research proposes several approaches, including the expansion of the concept of criminal law subject, the development of a layered liability model, and the reformulation of the form of criminal sanctions. In conclusion, comprehensive and interdisciplinary criminal law reform is needed to accommodate the reality of AI technology, while maintaining the fundamental principles of criminal law such as justice and legal certainty.